The voices that are gone : themes in nineteenth-century American popular song - Finson, Jon W. (Oxford University Press, 1997)
Jon Finson views the mores and values of 19th-century Americans as they appear in their popular songs. Presenting a guided tour of topically arranged, select songs, he points out the most important landmarks, as well as lesser sights that provide colour and context, and obscure but treasurable parts of the scenery previously overlooked.